2011
DOI: 10.4028/www.scientific.net/msf.695.247
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Crack Sensitivity and Gap Bridging Ability during Laser Butt Welding of Aluminum 5J32 and 6K21 Alloys

Abstract: Growing demand to reduce fuel consumption has accelerated the application of Al sheets to the body structure of automobiles. While recent studies on laser welding of Al 5xxx series and Al 6xxx series alloys have examined weldability, the laser autogenous welding usually results in low gap bridging capability and weld defects such as porosity, underfill, cracking, and so on. In this study, we evaluated the gap bridging capability and the crack sensitivity during laser autogenous welding, laser welding with fill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…In addition to the advantages of laser beam welding such as narrow welds, higher welding speed and deeper weld penetration that can be realised in laser arc hybrid welding, it has been reported that the combination of laser beam and arc results in other advantages such as better gap bridgeability and better metallurgical properties due to welding wire addition. 25,26 A general assessment of the laser arc hybrid welds produced in IN738 superalloy in the present work suggests that laser arc hybrid welding has great potentials for improving the weldability of nickel based superalloys. Nevertheless, safety demands on aero gas turbine components require the manufacturing of high quality welds during fabrication and repair of components.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…In addition to the advantages of laser beam welding such as narrow welds, higher welding speed and deeper weld penetration that can be realised in laser arc hybrid welding, it has been reported that the combination of laser beam and arc results in other advantages such as better gap bridgeability and better metallurgical properties due to welding wire addition. 25,26 A general assessment of the laser arc hybrid welds produced in IN738 superalloy in the present work suggests that laser arc hybrid welding has great potentials for improving the weldability of nickel based superalloys. Nevertheless, safety demands on aero gas turbine components require the manufacturing of high quality welds during fabrication and repair of components.…”
Section: Resultsmentioning
confidence: 68%
“…2). In addition to the advantages of laser beam welding such as narrow welds, higher welding speed and deeper weld penetration that can be realised in laser arc hybrid welding, it has been reported that the combination of laser beam and arc results in other advantages such as better gap bridgeability and better metallurgical properties due to welding wire addition 25,26…”
Section: Resultsmentioning
confidence: 99%
“…Solidification cracking has been evaluated for various fusion welding processes such as arc welding [ 5 , 6 , 7 ], electron beam welding [ 8 ], and laser beam welding [ 9 , 10 , 11 , 12 ]. Laser welding using a high-density laser beam can reduce heat input to a workpiece and minimize thermal distortion.…”
Section: Introductionmentioning
confidence: 99%